The Meaning of Career Success among Job-Hopper in The Boundaryless Career (Phenomenological Research) - Marcham Darokah Danita Irianti Malute (Journal of Educational, Health and Community Psychology, 2012)
Abstract  This phenomenology qualitative research was conducted in order to examine the dynamics of career success among job hopper and how did job hoppers interpret the meaning career success in boundaryless career. This research used in-depth interview for collecting the data and supported by the data from the documents. The respondents involved in this research were fours job hoppers in the level of manager, five significant others, such as family, workmate, and a steady career. The findings revealed that: the job-hoppers individuals who frequently movement of job from one place to another place because of intrinsic factors (financial, interpersonal conflict, alternative employment opportunities, etc.), extrinsic factors (challenges, willing to learn, personal characteristics, family, etc.), proponent factors (networking, family support, and media). The meanings of career success among job-hopper in the boundaryless career namely; self-fulfillment (job satisfaction, life satisfaction, meeting personal goals, adding value to others), and work/life balance (family satisfaction and quality time with family). This study showed that being a job-hopper was a tool for pursuing the meaning of career success. Keywords: Job-hopper, career success, boundaryless career, qualitative.